Best practice guidelines for rat eradication on tropical islands. (May 2015) - Keitt, B.; Griffiths, R.; Boudjelas, S.; Broome, K.; Cranwell, S.; Millett, J.; Pitt, W.; Samaniego-Herrera, A.
Highlights: Rat eradications on tropical islands fail more often than on tropical islands. A workshop was convened with 34 experts to identify possible solutions. Tracking island productivity and timing an eradication appropriately are key. Application strategies must account for bait competition and breeding rats. Information sharing and operational reporting are important for future improvement. Abstract: Invasive vertebrates are a leading cause of extinction on islands and rats ( Rattus spp.) are one of the most damaging to island ecosystems. Methods to eradicate rats from islands are well established and there have been over 580 successful eradications to date. Increasingly, rat eradications are being implemented on tropical islands, a reflection of the need to protect the threatened biodiversity in the tropics. Yet rat eradications on tropical islands fail more frequently than those in temperate climates. In an effort to identify the main reasons for the lower success rate on tropical islands and possible solutions, a workshop was convened with 34 experts in rat eradication, tropical rodent and island ecology and toxicology. The workshop focused on projects using aerial broadcast of brodifacoum, a 2nd generation anticoagulant, because this approach has provided the highest success rate for eradicating rodents from islands. The workshop participants reviewed previously identified challenges to successful rat eradications on tropical islands including increased insect and crab densities resulting in competition for bait, year round or unpredictable timing of breeding rats and increased or unpredictable availability of alternative, natural foods. They also identified a number of new, likely reasons for the lower success rate on tropical islands and provided recommendations for how to address these risks in the planning and implementation of rat eradications. While the success rate of aerial broadcast rat eradications in tropical environments is quite high at 89% ( n = 47), it is hoped that by following the recommended best practices provided in this paper, future success rates will be closer to the 96.5% ( n = 116) demonstrated for aerial broadcast rat eradications on temperate islands.